Saving the baby while discarding the bathwater: the application of policy coherence for development analysis to payment for watershed services - Koff, Harlan; Maganda, Carmen (Instituto de Ecología, A.C., 2019)
One of the most debated tools for the implementation of sustainable development is “payment for ecosystem services”, of which “payment for watershed services” (PWS) is one of the most developed. While proponents argue that such payments provide market value to the services that ecosystems provide for development, opponents claim that this approach commodifies the environment and promotes inequalities. This article presents an analysis of PWS programs by applying methodologies based on policy coherence for development (PCD), defined as a policy tool aimed at eliminating incoherence within sustainable development strategies that undermine their effectiveness as well as between such strategies and other policy arenas, which are also considered harmful to sustainability. By employing a PCD methodology, the article aims to identify policy mechanisms that undermine PWS programs so that stakeholders can make adjustments, thus, metaphorically ensuring that “the baby” (PWS) is not discarded with “the bathwater” (policy incoherence for sustainable development).